The shrinkage effect of formalin on renal cell carcinoma: Does it change the stages? - Akgul, Murat; Arslan, Aysegul Isal; Yazici, Cenk; Altin, Enes; Oznur, Meltem (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the shrinkage effect of formalin on renal cell carcinoma. Method: The retrospective study was conducted from October to November 2020 at Tekirdag Namil kemal University, Turkey and comprised all radical and partial nephrectomy cases performed by a single surgeon in a single clinic between January 2014 and August 2020. Preoperative images and postoperative pathology were reviewed by the same clinician. Preoperative longest tumour diameter of radiological images and pathological specimens measured after formalin fixation shrinkage were compared, and the effect of the difference between the two measurements on the circumference of the tumour was examined. The formalin related shrinkage rates of renal tumours according to the tumour size and the tumour types were also analysed. Data was analysed using SPSS 20. Results: Of the 101 cases, 58(57.4%) were of radical and 43(42.6%) of partial nephrectomy. Also, there were 77(76.2%) renal cell carcinoma cases, 22(21.8%) benign renal tumours and 2(1.9%) had other malignant tumours. There were 59(58.4%) males and 42(41.6%) females with an overall mean age of 58.1±12,2 years (range: 30-82 years). The mean radiological size of the renal tumours was 55.3±30.4mm and it was 52.9±31.6mm at pathological examination (p>0.05). Conclusion: Formalin fixation of tissues post-surgery caused a difference between the radiological and pathological dimensions. Though the difference was no significant, under-staging due to the shrinkage post-surgery should be considered. Key Words: Renal tumours, Tissue shrinkage, Formalin, radiological dimension, Pathological dimension. —Continue